Penguatan Pendidikan Karakter Siswa Melalui Pengembangan Budaya Sekolah di SDN 1 Jenangan - Aris Nurbawani; Endah Rahmawati; Sindy Oktavia Kartikasari; Siska Faridzatul Isnaini; Siti Mu’allifah (Progressive Journal of Educational Science, 2025)
Character education is an important part in forming students' personalities which must be implemented from an early age. Schools have a strategic role in developing character education through various activities and supportive school culture. Various character crisis phenomena that arise in schools make parents and teachers worry about their children's growth. Efforts are being made to overcome the problem of character crisis, SDN 1 Jenangan through cultural development. This type of qualitative descriptive research was used in this research to describe the implementation of character education in school culture at SDN 1 Jenangan. The results of the research show that the development of school culture at SDN 1 Jenangan can instill eighteen character values: religious, honest, tolerance, discipline, hard work, creative, independent, democracy, national spirit and nationalism, curiosity, love of the country, respect for achievement communicative, likes to read, cares about the environment, cares about socialissues, love peace and is responsible for students in accordance with community values and norms.